Kinase/phosphatase overexpression reveals pathways regulating hippocampal neuron morphology - William J Buchser; Tatiana I Slepak; Omar Gutierrez‐Arenas; John L Bixby; Vance P Lemmon (Molecular Systems Biology)
Abstract Development and regeneration of the nervous system requires the precise formation of axons and dendrites. Kinases and phosphatases are pervasive regulators of cellular function and have been implicated in controlling axodendritic development and regeneration. We undertook a gain‐of‐function analysis to determine the functions of kinases and phosphatases in the regulation of neuron morphology. Over 300 kinases and 124 esterases and phosphatases were studied by high‐content analysis of rat hippocampal neurons. Proteins previously implicated in neurite growth, such as ERK1, GSK3, EphA8, FGFR, PI3K, PKC, p38, and PP1a, were confirmed to have effects in our functional assays. We also identified novel positive and negative neurite growth regulators. These include neuronal‐developmentally regulated kinases such as the activin receptor, interferon regulatory factor 6 (IRF6) and neural leucine‐rich repeat 1 (LRRN1). The protein kinase N2 (PKN2) and choline kinase α (CHKA) kinases, and the phosphatases PPEF2 and SMPD1, have little or no established functions in neuronal function, but were sufficient to promote neurite growth. In addition, pathway analysis revealed that members of signaling pathways involved in cancer progression and axis formation enhanced neurite outgrowth, whereas cytokine‐related pathways significantly inhibited neurite formation.